Clinical study of polycystic ovarian syndrome (PCOS) in tertiary care centre - D., Sowmya; S., Anitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A true definition of polycystic ovarian syndrome involves a blending of the morphological and histological ovarian changes with endocrine abnormalities associated with these changes. Objective of present study was to detect the differences among women with PCOS and without PCOS. Methods: Twenty-five subjects with PCOS were included in the study on first cum first basis and twenty-five non PCOS subjects just next to each PCOS cases were included as control group. Results: Mean age of PCOS and Non PCOS subjects were 42.68 and 43.88 years respectively. Sixteen percentage of PCOS were from higher socio-economic status, which was statistically significant. PCOS subjects had 96% hirsuitism, 48% acne, 4% heavy voice and breast atropy which was also statistically significant. Conclusions: Women with PCOS have a hormonal imbalance and metabolism problems that may affect their health and fertility, we found PCOS subjects are more in urban population with strong family history. Lifestyle modification and dietary modification helps for the long-term health prognosis. women who are at risk of PCOS to be educated and managed for the continuing health risk and planned potential therapeutic strategies. Further research has to look into possibility of genes linked into PCOS.